2017
DOI: 10.12996/gmj.2017.22
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Relationship Between Type of Disability and Labor Force Participation: A Community Based Study in Iran

Abstract: ÖZETBu çalışmada, engelliliğin hangi tipinin işgücüne katılım üzerinde daha fazla etkili olduğunu bulmaya çalıştık. Bu çalışmada İran'ın on ilindeki özürlü bireylerden oluşan 1500 kişilik bir toplum verisi kullanılmıştır. Engellilik türünün işgücüne katılım üzerindeki etkilerini göstermek için lojistik model kullanılmıştır. Modelde cinsiyet, yaş, evlilik durumu, eğitim, normal yaşama gücü ve iletişim yeteneği ayarlandı. Bu çalışmanın sonuçları zihinsel engelli ve kalıtıma bağlı olarak engelli olan kişilerin di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…The positive Cramér coefficient on education indicates that the higher the education, the higher the employment opportunities. Similarly, a previous study in Iran showed that education level has a positive effect on labour participation for people with disabilities, with greater opportunities for university graduates (Rad et al, 2017). Meanwhile, in the non-disabled group, weak (Thomas, 2022).…”
Section: Disabilitymentioning
confidence: 75%
“…The positive Cramér coefficient on education indicates that the higher the education, the higher the employment opportunities. Similarly, a previous study in Iran showed that education level has a positive effect on labour participation for people with disabilities, with greater opportunities for university graduates (Rad et al, 2017). Meanwhile, in the non-disabled group, weak (Thomas, 2022).…”
Section: Disabilitymentioning
confidence: 75%